Genomic differentiation of three pico‐phytoplankton species in the Mediterranean Sea. (24th August 2022) - Da Silva, Ophélie; Ayata, Sakina‐Dorothée; Ser‐Giacomi, Enrico; Leconte, Jade; Pelletier, Eric; Fauvelot, Cécile; Madoui, Mohammed‐Amin; Guidi, Lionel; Lombard, Fabien; Bittner, Lucie
Abstract: For more than a decade, high‐throughput sequencing has transformed the study of marine planktonic communities and has highlighted the extent of protist diversity in these ecosystems. Nevertheless, little is known relative to their genomic diversity at the species‐scale as well as their major speciation mechanisms. An increasing number of data obtained from global scale sampling campaigns is becoming publicly available, and we postulate that metagenomic data could contribute to deciphering the processes shaping protist genomic differentiation in the marine realm. As a proof of concept, we developed a findable, accessible, interoperable and reusable (FAIR) pipeline and focused on the Mediterranean Sea to study three a priori abundant protist species: Bathycoccus prasinos, Pelagomonas calceolata and Phaeocystis cordata . We compared the genomic differentiation of each species in light of geographic, environmental and oceanographic distances. We highlighted that isolation‐by‐environment shapes the genomic differentiation of B. prasinos, whereas P. cordata is impacted by geographic distance (i.e. isolation‐by‐distance). At present time, the use of metagenomics to accurately estimate the genomic differentiation of protists remains challenging since coverages are lower compared to traditional population surveys. However, our approach sheds light on ecological and evolutionary processes occurring within natural marine populations and paves the way for future protist population metagenomic studies.